Reconstitution of the 80-pillared hall in Pataliputra - Wiki commons (2022)
Reconstitution of the 80-pillared hall in Pataliputra, where the Third Buddhist Council may have taken place. Patna Museum. Image courtesy: By Hpgoa - Flickr [1], CC BY-SA 2.0, https://commons.wikimedia.org/w/index.php?curid=70984689